Healthcare System Failure Cured by ‘Empower Patients’ - Deane Waldman (Health Economics and Management Review)
Historical evidence and current experience suggest the U.S. healthcare face several actual challenges. National healthcare spending – $4.8 trillion in 2023, 17.6 % of GDP – is unsustainable, constantly increasing the national debt. Average family health care costs of $31,065 per household in 2023 are unaffordable. As government regulations rise and administrative processes expand, access to medical care decreases. This previously unrecognized inverse relationship is called the seesaw relationship. Necessary medical care is so delayed that Americans experience death-by-queue. Medical autonomy has become tense, as exposed by the federal response to the COVID-19 threat. Systems theory exposes government regulations as “fixes-that-fail-or-backfire”. The prevailing cause of healthcare system’s progressive failure is central economic control that suppresses the free market. The third-party payment system separates patients from their own funds as well as their right to choose their own care. Consumers or patients, who are buyers but not payers, have no incentive to save. Sellers (providers of care) do not compete for consumers’ funds. Sellers’ prices or charges have no relevance as allowable reimbursement schedules, issued by federal government, determine what sellers are paid. The solution for critical problems of the U.S. healthcare system is to take decision-making authority away from federal authorities and return it to patients. In other words, the U.S. medical system needs to reconnect patients – buyers in the healthcare marketplace – with both their money and their doctors, thus restoring patients’ medical autonomy. This approach has been named “Empower Patients”. By dissolving the root cause, the Empower Patients program will produce timely and affordable medical care, restore medical autonomy, and could potentially save $2 trillion in U.S. “healthcare” spending. Empower patients will be equally effective in other government-run, failing single payer healthcare systems such as Great Britain’s National Health Service.